2016
DOI: 10.7196/samj.2016.v106i3.9969
|View full text |Cite
|
Sign up to set email alerts
|

Providers’ perceptions of the implementation of a performance measurement system for substance abuse treatment: A process evaluation of the Service Quality Measures initiative

Abstract: Background. In South Africa, concerns exist about the quality of substance abuse treatment. We developed a performance measure ment system, known as the Service Quality Measures (SQM) initiative, to monitor the quality of treatment and assess efforts to improve quality of care. In 2014, the SQM system was implemented at six treatment sites to evaluate how implementation protocols could be improved in preparation for wider roll-out. Objective. To describe providers' perceptions of the feasibility and acceptabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Additionally, interpretation of the EBPAS scales would be further enhanced by qualitative evaluations of barriers to adopting new evidence-based practices. Although qualitative research was conducted as part of this initiative 25 , it was separate from the current study. Further research would benefit from mixed methods evaluations of factors influencing readiness to adopt new evidence-based practices.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, interpretation of the EBPAS scales would be further enhanced by qualitative evaluations of barriers to adopting new evidence-based practices. Although qualitative research was conducted as part of this initiative 25 , it was separate from the current study. Further research would benefit from mixed methods evaluations of factors influencing readiness to adopt new evidence-based practices.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the pilot implementation of the SQM system was preceded by an intensive community engagement phase that included a series of focus group discussions with treatment providers, presentations at treatment facilities to discuss the need for such a system, and marketing by means of posters and information brochures. [6][7][8] Collectively, RESEARCH these activities could have enhanced awareness and acceptance of the SQM system among treatment staff, partially accounting for the high degree of readiness to adopt the SQM initiative observed among this sample of treatment providers. We also found that leadership support for the implementation of the SQM initiative was strongly associated with readiness to adopt; this effect prevailed even after controlling for other potential influences on system implementation.…”
Section: Discussionmentioning
confidence: 99%
“…[13] In addition to providing staff with training in the implementation of the SQM system, [8] we provided facility-wide training and information on the purpose and benefits of performance measurement as well as the organisation's need for such a system. Building awareness of the organisation's need for a performance measurement system and the associated benefits to the individual and organisation, arguably enhanced treatment providers' readiness to adopt the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this gap, we developed a performance measurement system for South Africa’s SUD treatment system known as the Service Quality Measures (SQM) initiative. The development and initial implementation of this system is described elsewhere (Myers et al, 2015, 2016b).…”
mentioning
confidence: 99%